The Effect of Profitability, Liquidity, and Solvency on the Value of Health Companies Listed On the Indonesia Stock Exchange - Rukhiyatul Jannah; Anita Handayani (Universitas Muhammadiyah Gresik, 2022)
Abstract Background - Corporate Value is a certain condition that has been achieved by a company as an illustration of the public's trust in the company that has gone through a process of activity for several years. Since the company was founded until now.Objective – to determine the impact of profitability, liquidity, and solvency on company value in health companies listed on the Indonesia Stock Exchange in 2017 – 2020.Design / methodology / approach - The type of research used is a quantitative research type, namely information data from financial statements in the form of numbers or figures. The sampling method used panel data, namely data that used a combination of cross-sectional data with time series data, based on the population, the study was conducted on 10 health companies and 4 years of observation starting from 2017 - 2020 so that the total data 40 companies (10 companies x 4 years). The data collection technique uses documentation from financial reports published on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis technique used is multiple linear regression.Findings - The results of this study indicate that profitability has a significant and positive effect on firm value, liquidity has a significant and positive effect on firm value, solvency has a significant and positive effect on firm value. Keyword: Profitability, Liquidity, Solvency, and Firm Value